Expression of Intracellular Galectin-8 and -9 in Endometrial Cancer - Beyer, Susanne; Wehrmann, Maya; Meister, Sarah; Trillsch, Fabian; Ganster, Franziska; Schmoeckel, Elisa; Corradini, Stefanie; Mahner, Sven; Jeschke, Udo; Kessler, Mirjana; Burges, Alexander; Kolben, Thomas (International Journal of Molecular Sciences, 2024)
Endometrial cancer (EC) is a common gynecological cancer worldwide. Treatment has been improved in recent years; however, in advanced stages, therapeutic options are still limited. The expression of galectins is increased in several tumor types and that they are involved in important cell processes. Large studies on endometrial cancer are still pending; Specimens of 225 patients with EC were immunohistochemically stained with antibodies for Gal-8 and Gal-9. Expression was correlated with histopathological variables. The cytosolic expression of both galectins is associated with grading and survival. Cytosolic Galectin-8 expression is a positive prognostic factor for overall survival (OS) and progression-free survival (PFS), while nuclear Gal-8 expression correlates only to OS. The cytosolic presence of Galectin-9 is correlated with a better prognosis regarding OS. Our results suggest that expression of both galectins is associated with OS and PFS in EC. Further studies are needed to understand the underlying molecular mechanisms.
CRIS-Team Scopus Importer:2025-10-13
Keywords: biomarker; endometrial cancer; Gal-8; Gal-9; prognosis; survival